Lactose free milk and dairy product purchasing habit variables of Bangkok Thailand metropolitan consumers - Senadisai, Panja; Trimetsoontorn, Jirasek; Fongsuwan, Wanno (My University, 2015)
With upwards of 90% of Asians unable to ingest milk products, lactose free milk can be a major contributor to a nation's health and weilbeing. Thailand, a country in Southeast Asia with nearly 70 million citizens is a market with almost no commercially available lactose free products for adult consumers with only limited lactose free milk children's milk products currently available. Given the importance of calcium to healthy development and growth, the researchers therefore undertook this study to determine the variables on the consumption and purchase intention of lactose free milk and dairy products within the Bangkok metropolitan area. Quantitative data was obtained from 189 Bangkok consumers over 18 years old and qualitative data from in-depth interviews of 10 nutritional experts, a doctor, marketers and patients while using Partial Least Square (PLS-Graph) software to apply Structural Equation Modeling (SEM) analysis. The results showed that the factor with the greatest influence on lactose free milk purchase intention included milk knowledge about lactose free milk as well as consumer marketing and the packaging and product reputation which have both direct and indirect influencing factors on lactose free milk purchasing and consumption.
Keywords: Lactose free; management; Milk; Purchase intention